On the limits of cheap talk for public good provision - Costa, Francisco Junqueira Moreira da (2008)
This article studies a model where, as a consequence of private information, agents do not have incentive to invest in a desired joint project, or a public good, when they are unable to have prior discussion with their partners. As a result, the joint project is never undertaken and inefficiency is observed. Agastya, Menezes and Sengupta (2007) prove that with a prior stage of communication, with a binary message space, it is possible to have some efficiency gain since 'all ex-ante and interim efficient equilibria exhibit a simple structure'. We show that any finite message space does not provide efficiency gain on the simple structure discussed in that article. We use laboratory experiments to test these results. We find that people do contribute, even without communication, and that any kind of communication increases the probability of project implementation. We also observed that communication reduces the unproductive contribution, and that a large message space cannot provide efficiency gain relative to the binary one.